Sociological Analysis of the Sati System: A Reflection of the Mahabharata and the Pret Kalp of the Garudamahapurna in Gender Perspective - Adhikari, Shukra Raj; Adhikari, Bhawani Shankar; Acharya, Ganga (Molung Educational Frontier, 2025)
Sati (wives burning alive with the dead bodies of their husbands on the pyres as their deceased husbands’ bodies are burnt down in the burning ghat) system was performed as norms and rules of the society in the patriarchal socio-cultural structure in the past era. This research has been focused on exploring the Sati system in terms of the women's roles in the death ritual of the historical period of The Mahabharata and Pauranic era of The Pret Kalpa of The Garudmahaapurana. There is no possibility to visit the historical period of society. Each piece of knowledge and literature has been socially produced. The literature reflects the socio-cultural relationship of that period of society. Method: This research has gathered historical data using the historical content analysis method and expert interviews.Similarly, secondary data has been collected through the articles, published in various journals of related issues. The content analysis method was applied to analyze the data using the qualitative research design. The legacy of Sati transcends its historical confines, catalyzing ongoing conversations about gender equity and human rights in a contemporary context. Exploration of the sati system through the ancient scriptures like The Mahabharata and The Preta Kalpa of The Garudamahapurana has given the knowledge of how gender issues have been shaped, guided, and passed on and on from generation to generation to the present social and cultural practices. The data have been analog to the theoretical assumption of patriarchy.